Qualitative behavior of solutions of Liénard-type systems with state-dependent impulses. (October 2022) - Sugie, Jitsuro; Zhao, Xin
Abstract: State-dependent impulsive differential equations can be used to describe phenomena in which the velocity of an object suddenly changes when the object enters a predetermined state. This study examines the effect of state-dependent impulses on the rotation of all orbits of the Liénard system, which plays an important role in many research areas, including electrical circuits, diverse engineering fields, economics, ecology, and physiology. Determining whether all orbits of the Liénard system other than the origin, which is the only fixed point, rotate around the origin, is the basis of other properties of the orbit and has become a significant research subject; however, very few studies have examined the effects of state-dependent impulses on this behavior, and the main theorem presented in this paper addresses this. This rotation problem is reduced to establishing whether all orbits intersect the vertical isocline, which is discussed in detail. To facilitate the understanding of the proof of the main theorem, an overview is presented before providing the actual proof. The main theorem and some lemmas are proved using phase plane analysis. The application of the main theorem to Euler's equations is also described. Highlights: State-dependent impulses affect the rotation of all orbits of a Liénard system. Despite the importance of Liénard systems, few studies have examined these impulses. The rotation problem is reduced to whether all orbits intersect the vertical isocline. Phase plane analysis is used to prove the main theorem and associated lemmas. In addition, the main theorem is applied to Euler's equation.